EVALUATE THE EFFECTIVENESS OF COLD APPLICATION PRIOR TO INTRAMUSCULAR IMMUNIZATION ON REDUCING PAIN AMONG INFANTS AT CHENNAI - Sasikala. G; K. Mythili; Vincy selwyn; Florence Nightingale. K. A; Jothimeena. B (The Bioscan, 2026)
Introduction: Vaccination to children at the right time so they develop antibodies that provide strong immunity. During Vaccination in infants can cause mild discomfort, such as redness, swelling, and fussiness, which usually resolves within a couple of days. These reactions are common and temporary, but it’s important to manage the pain and discomfort for the infant’s well-being. Cold application helps in the treating of injury which reduce swelling and pain. Methodology: This study involved 60 infants, divided into two groups a study group (30 infants) and a control group (30 infants). The study group received cold therapy following vaccination, while pain levels in both groups were measured using the Neonatal Infant Pain Scale (NIPS). Conclusion: Cold application effectively reduced pain in infants following vaccinations. This simple and easy-to-apply method can help manage discomfort after immunization. Given its effectiveness, healthcare providers should consider incorporating cold therapy as part of pain management strategies during vaccinations to improve the comfort of infants. Keywords Cold Application, Infant, Vaccination, Immunization, Intramuscular